A critical analysis of resetting decision making in any organization - Reidhead, Christine (Technium Social Sciences Journal, 2021)
The role of management is very important in the strategic growth and development of any organization in the long run. Important decision making is a critical factor for the strategic planning of organizational vision and mission. There are times when this important factor needs to be relooked from the fresh pair of eyes and apply the learning from past experience to reset it to suit the current requirements. This paper talks about the critical analysis of resetting decision making in any organization. Secondary analysis has been done for different organizations to understand the role of factors impacting the decision making process in an organization and how team performance and targets are set. The aims and objectives of the companies have been studied and critically analyzed to see if this is in accordance with the strategic objectives of the company. The study of decision making for different companies have given an in-depth focus to this research and have highlighted the entire process of working a management team in an organization.